Impacts of monetary and fiscal policy interaction on economic growth and inflation, and the Taylor rules in Malaysia, Thailand and Singapore - Tan, Chai Thing (2019)
Macroeconomic policies play an important role in stabilising prices and growth. Recent financial crises have raised awareness of the role of the interaction of monetary and fiscal policies. This study examines the interaction of monetary and fiscal policies in three countries namely; Malaysia, Thailand and Singapore from 1980: Q1 until 2017: Q1. The first objective of this study was to examine the interaction of monetary and fiscal policies on economic growth. The results revealed that the long-run relationship between monetary policy and output was positive for all three countries while the long-run relationship between fiscal policy and output was positive in the case of Thailand. However, its interaction with the interest rate and government spending was found to be important for economic growth. The result indicated that the interaction term between monetary and fiscal policies had a negative effect on economic growth in Malaysia and Thailand but had a positive effect in Singapore. This evidence suggested that the effects of monetary policy (fiscal policy) on economic growth were altered by different levels of government spending (interest rate). In other words, the expansion of one policy could deal more efficiently with growth with the interaction of another policy. By examining the interaction of the policies on inflation, the results of the second objective show that the relationship between monetary policy and inflation was negative in Singapore while fiscal policy had a positive effect on inflation in Malaysia and Thailand. The interaction term between monetary and fiscal policy had a positive effect on inflation in Malaysia but had a negative effect on inflation in Singapore and Thailand. This indicates that the effectiveness of one policy will be influenced by changes in the level of another policy. Thus, regardless of the country, the interaction of monetary and fiscal policy played an important role in influencing the effectiveness of another policy. Separating monetary and fiscal policies will overlook the importance of policy interaction on stimulating economic growth and inflation. It is important to take into account the potential interaction between monetary and fiscal policy for good policy-making (Sims, 2011). These first two objectives were estimated by using the ARDL approach. The third strand of this thesis examined the Taylor rules by using the Generalized Method of Moments (GMM) approach. The results showed that; (i) Backwards looking Taylor rules in Malaysia and Thailand seem to provide a reasonable description of central bank behaviour while forward-looking Taylor rules apply in Singapore. This means that past inflation and the output gap play a role in influencing the monetary policy reaction function in Malaysia and Thailand. (ii) The Augmented Taylor rule incorporating the exchange rate and government spending best describes the behaviour of interest rate setting in Malaysia, Thailand and Singapore. (iii) The monetary authorities in these economies respond positively to inflation (except for Singapore) and the output gap, however, the coefficient of the inflation rate was lower than 1.5 as postulated by Taylor (1993). In addition, the results indicated central banks in all three countries have a strong preference for implementing the monetary policy rules towards interest rate smoothing, government spending and the exchange rate.